2016
DOI: 10.18632/oncotarget.12334
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 is a DNA damage response protein that regulates cellular sensitivity to PARP inhibitors

Abstract: Liver kinase B1 (LKB1) functions as a tumor suppressor encoded by STK11, a gene that mutated in Peutz-Jeghers syndrome and in sporadic cancers. Previous studies showed that LKB1 participates in IR- and ROS-induced DNA damage response (DDR). However, the impact of LKB1 mutations on targeted cancer therapy remains unknown. Herein, we demonstrated that LKB1 formed DNA damage-induced nuclear foci and co-localized with ataxia telangiectasia mutated kinase (ATM), γ-H2AX, and breast cancer susceptibility 1 (BRCA1). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 61 publications
(65 reference statements)
2
33
0
Order By: Relevance
“…We sought to take advantage of LKB1 deficiency in the context of DNA damage/repair, and our data suggest that patient tumors harboring mutant KRAS with loss of LKB1 may respond more effectively to WEE1 inhibition, either alone or in combination with DNA-damaging therapies. Recent work by Wang and colleagues (34) demonstrated that LKB1-deficient cells were more sensitive to PARP inhibitors, and that LKB1 could interact with ATM and BRCA1 as part of the DNA damage response pathway. Our data also suggest that T366, a phosphorylation site for ATM on LKB1 is necessary for the resistance conferred by wild-type LKB1 to AZD1775 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to take advantage of LKB1 deficiency in the context of DNA damage/repair, and our data suggest that patient tumors harboring mutant KRAS with loss of LKB1 may respond more effectively to WEE1 inhibition, either alone or in combination with DNA-damaging therapies. Recent work by Wang and colleagues (34) demonstrated that LKB1-deficient cells were more sensitive to PARP inhibitors, and that LKB1 could interact with ATM and BRCA1 as part of the DNA damage response pathway. Our data also suggest that T366, a phosphorylation site for ATM on LKB1 is necessary for the resistance conferred by wild-type LKB1 to AZD1775 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these functions contribute to the induction of epithelial mesenchymal transition (EMT) and metastasis 27 , 28 . In addition to this, in vivo experiments have shown evidence for the contribution of LKB1 to genotoxic DNA damage response and DNA damage repair 12 , 29 .…”
Section: Introductionmentioning
confidence: 90%
“…As mentioned above mutations in STK11/LKB1 and consequential disruption of AMPK signaling pathways are amongst the most frequent aberrations in lung cancers [reviewed in (94)]. Both LKB1 and AMPK have been suggested to have roles in DNA repair pathways, however the full extent of the influence of LKB1 downregulation on DNA repair pathways in lung cancer has not yet been explored (95,96).…”
Section: Dna Double-strand Break Repairmentioning
confidence: 99%